COVID Vaccine Transport, Storage, and Distribution: Cold Chain Management to Ensure Efficacy - Michael Rusnack (University of Minnesota Libraries Publishing, 2021)
The Vaccines for Children Program (VFC) is a federally funded program in the United States, providing vaccines to children who lack health insurance or who otherwise cannot afford the vaccination cost. The VFC program was created in 1993 and is required to be a new entitlement of each State's Medicaid plan. The program was officially implemented in October 1994 and served eligible children in all United States (US). Other countries, the United Nations (UN), and the World Health Organization (WHO), have similar programs.  A critical aspect of these programs is the guidance surrounding the environmental monitoring of the materials. To best maintain the integrity of these products, specific storage parameters are required. It is necessary to store most vaccines at refrigeration or freezing temperatures. To best assure the efficacy of the vaccines, monitoring standards and equipment are specified. The technology and methodologies may be adequate for these programs' materials; these same methods are not for the COVID vaccine.[1]  When reviewing the guidance recommendations worldwide, one may observe commonalities in the program. Each guidance calls for the use of digital data loggers (DDL), sampling rates of 15 to 30 minutes, daily check-in (during business hours), and the use of a temperature buffer, each without specificity.[2] The inadequacies of the VFC program monitoring methodologies fall far short when monitoring COVID vaccines. Herein considerations for the transport, storage, and distribution of the COVID vaccine cold chain will be discussed.